Small RNA and Degradome Deep Sequencing Reveals the Roles of microRNAs in Peanut (Arachis hypogaea L.) Cold Response - Zhang, Xin; Ren, Chao; Xue, Yunyun; Tian, Yuexia; Zhang, Huiqi; Li, Na; Sheng, Cong; Jiang, Huifang; Bai, Dongmei (Frontiers in Plant Science, 2022)
Cold stress is a major environmental factor that affects plant growth and development, as well as fruit postharvest life and quality. MicroRNAs (miRNAs) are a class of non-coding small RNAs that play crucial roles in various abiotic stresses. Peanuts (Arachis hypogaea L.), one of the most important grain legumes and source of edible oils and proteins, are cultivated in the semi-arid tropical and subtropical regions of the world. To date, there has been no report on the role of miRNAs in the response to cold stress in cultivated peanuts. In this study, we profiled cold-responsive miRNAs in peanuts using deep sequencing. A total of 407 known miRNAs and 143 novel peanut-specific miRNAs were identified. The expression of selected known and novel miRNAs was validated by northern blotting and six known cold-responsive miRNAs were revealed. Degradome sequencing identified six cold-responsive miRNAs that regulate 12 target genes. The correlative expression patterns of several miRNAs and their target genes were further validated using qRT-PCR. Our data showed that miR160-ARF, miR482-WDRL, miR2118-DR, miR396-GRF, miR162-DCL, miR1511-SRF, and miR1511-SPIRAL1 modules may mediate cold stress responses. miR160, miR482, and miR2118 may play positive roles, and miR396, miR162, and miR1511 play negative roles in the regulation of peanut cold tolerance through related target genes in peanuts. Our results provide a foundation for understanding miRNA-dependent cold stress response in peanuts. The characterized correlations between miRNAs and their response to cold stress could serve as markers in breeding programs or tools for improving cold tolerance of peanuts.